Negotiating Sikh Identity in Pakistan: State Policies, Minority Citizenship, and Religious Recognition (1947–2025) - Fatimah Saleem (Policy Journal of Social Science Review, 2026)
This article explores the Sikh identity in Pakistan from the partition in 1947 to the present. It looks at institutional practices, governmental policies, and constitutional requirements and their impact on the Sikh minority as citizens. The article argues that the Sikhs of Pakistan are placed in a paradoxical situation as institutionally and officially recognised citizens of Pakistan. Yet, they continue to be marginalised by institutional neglect, forced conversions, and the decay of religious heritage. It does this by relying on the analysis of the constitution, demographic data, and information from human rights groups. Sikhs have now declined from a few hundred thousand in 1947 to around 16,000 due to migration and ongoing persecution. The Evacuee Trust Property Board, set up to manage minority religious properties, has not been able to reverse the slide of Sikh history, with only 37 out of 1817 gurdwaras remaining. Religious freedom is enshrined in the constitution of Pakistan, but its reality shows how little freedom there is for the religious minorities in a state whose identity is bound to Islam. The paper argues that there is a need for meaningful political representation in addition to reserved seats, institutional changes, and the retention of religious monuments to be able to acknowledge Sikh identity over the long term. Keywords: Sikh identity, Pakistan, minority rights, citizenship, religious freedom, forced conversion, Evacuee Trust Property Board, constitutionalism